Plasma Soluble Urokinase-Type Plasminogen Activator Receptor Is Not Associated with Neurological Outcome in Patients with Aneurysmal Subarachnoid Hemorrhage - Kiiski, Heikki; Jalkanen, Ville; Ala-Peijari, Marika; Hämäläinen, Mari; Moilanen, Eeva; Peltola, Jukka; Tenhunen, Jyrki (Frontiers in Neurology, 2017)
Object Aneurysmal subarachnoid hemorrhage (aSAH) is a common cause of death or long-term disability. Despite advances in neurocritical care, there is still only a very limited ability to monitor the development of secondary brain injury or to predict neurological outcome after aSAH. Soluble urokinase-type plasminogen activator receptor (suPAR) has shown potential as a prognostic and as an inflammatory biomarker in a wide range of critical illnesses since it displays an association with overall immune system activation. This is the first time that suPAR has been evaluated as a prognostic biomarker in aSAH. Methods In this prospective population-based study, plasma suPAR levels were measured in aSAH patients (n = 47) for up to 5 days. suPAR was measured at 0, 12, and 24 h after patient admission to the intensive care unit (ICU) and daily thereafter until he/she was transferred from the ICU. The patients’ neurological outcome was evaluated with the modified Rankin Scale (mRS) at 6 months after aSAH. Results suPAR levels (n = 47) during the first 24 h after aSAH were comparable in groups with a favorable (mRS 0–2) or an unfavorable (mRS 3–6) outcome. suPAR levels during the first 24 h were not associated with the findings in the primary brain CT, with acute hydrocephalus, or with antimicrobial medication use during 5-days’ follow-up. suPAR levels were associated with generally accepted inflammatory biomarkers (C-reactive protein, leukocyte count). Conclusion Plasma suPAR level was not associated with either neurological outcome or selected clinical conditions. While suPAR is a promising biomarker for prognostication in several conditions requiring intensive care, it did not reveal any value as a prognostic biomarker after aSAH.